Chartergellus jeannei, a New Species of the Swarming Social Wasps from the Amazon Forest ( Hymenoptera: Vespidae: Epiponini) - Grandinete, Y. C.; Andena, S. R.; Soleman, R. A. [UNESP]; Noll, F. B. [UNESP] (Univ Estadual Feira Santana, 2015)
A new species, Chartergellus jeannei Andena &Soleman, is described.
Keywords: Chartergellus; Epiponini; Amazon Forest; Army Ants